2020
DOI: 10.1089/bfm.2019.0243
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Factors Related to Infant Motor Development at 4 Months of Age

Abstract: Background: Exercise during pregnancy and breastfeeding after pregnancy both positively influence a number of infant outcomes. However, whether physical activity during late pregnancy and breastfeeding postpartum influence motor development in the offspring at 4 months of age is unknown. Research Aim: The purposes of this study were to investigate the relationships between several important modifiable factors (i.e., maternal physical activity during late pregnancy and breastfeeding after pregnancy) on infant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Although some studies indicate that women participating in exercise programs had children with greater motor skills scores 35 and born with increased brain maturation, 36 other studies indicate no effects of regular exercise during pregnancy on neurodevelopment of offspring at 18 months and 7 years 20,34 and no relationship between levels of physical activity and offspring motor development at 4 months. 37 These differential effects have even been observed in the same setting-data from the 2004 Pelotas Birth Cohort showed positive associations between PA during pregnancy and neurodevelopment at 12 months of the child; however, at 24 and 48 months, no association was observed. 19 Although our results indicate benefits of the exercise program during pregnancy only for the language and cognitive scores of the offspring, detrimental effects on children's development have not been previously demonstrated.…”
Section: Discussionmentioning
confidence: 85%
“…Although some studies indicate that women participating in exercise programs had children with greater motor skills scores 35 and born with increased brain maturation, 36 other studies indicate no effects of regular exercise during pregnancy on neurodevelopment of offspring at 18 months and 7 years 20,34 and no relationship between levels of physical activity and offspring motor development at 4 months. 37 These differential effects have even been observed in the same setting-data from the 2004 Pelotas Birth Cohort showed positive associations between PA during pregnancy and neurodevelopment at 12 months of the child; however, at 24 and 48 months, no association was observed. 19 Although our results indicate benefits of the exercise program during pregnancy only for the language and cognitive scores of the offspring, detrimental effects on children's development have not been previously demonstrated.…”
Section: Discussionmentioning
confidence: 85%
“…Although current literature emphasizes the significance of exercise during pregnancy 44 , 45 , prevalence of sport PA during pregnancy is known to be generally low in China 15 . Exercise requirements increase in the latter trimester of pregnancy to more effectively suppresses body fat accumulation and weight gain 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Key limitations of this scoping review are that we only included studies published in the English language and only focused on elements of offspring brain and neurodevelopment that relate to neurocognition (i.e., we did not include studies that only reported on offspring motor development 99,100 or behaviour 101 ). While the scoping review protocol was not prospectively registered and a formal assessment of methodological quality of the included studies was not performed, this is in accordance with guidelines for the conduct of scoping reviews 34,35 .…”
Section: Discussionmentioning
confidence: 99%